Determinan Pengungkapan Tanggung Jawab Sosial Perusahaan Dalam Sustainability Report - Anandita Zulia Putri (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2019)
This study examines the factors which influences disclosure of corporate social responsibility in sustainability report on mining companies that listed in Indonesia Stock Exchange. disclosure of corporate social responsibility in sustainability report on mining companies is important issue because mining companies that are closely related to the use of natural resources directly start to engage in a balance between the purpose of obtaining profits and environmental preservation. The sample was all mining companies that disclosure of corporate social responsibility in sustainability report for three years from 2015 until 2017 periods. The factors are profitability, liquidity, leverage, audit committee, board of directors. This study uses purposive sampling to select the sample. This research analyzed using multiple linear regression. Going concern opinion is significantly influenced by profitability, liquidity, audit committee, and board of directors. In the other hand, leverage don’t give effect to disclosure of corporate social responsibility in sustainability report on mining companies.